2021
DOI: 10.3390/ijerph18084286
|View full text |Cite
|
Sign up to set email alerts
|

Influential Factors of Masticatory Performance in Older Adults: A Cross-Sectional Study

Abstract: While appropriate nutrient intake is important for older adults, various oral problems cause decreased masticatory function. This cross-sectional study aimed to identify the factors associated with decreased masticatory performance in older adults. Oral examinations were performed on 80 participants (mean age: 75.10 ± 5.64 years) to determine the number of functional tooth units (FTUs). Symptoms of periodontal and temporomandibular diseases were evaluated via a questionnaire. The tone, elasticity, and dynamic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…50 The replacement of missing teeth through various forms of prosthodontic treatment was significantly the most common protective factor against masticatory dysfunction. 4,10,12,[51][52][53][54][55][56][57][58] Studies observed significant increases in prefrontal activity, masticatory muscle activity and occlusal force when wearing a denture, compared to non-denture wearers having marked prefrontal deactivation, decreased masticatory muscle activity and occlusal force. 53 A randomised controlled trial also revealed that both balanced and lingualised occlusal schemes in removable dentures had an equal positive effect on food comminution.…”
Section: Re Sultsmentioning
confidence: 99%
“…50 The replacement of missing teeth through various forms of prosthodontic treatment was significantly the most common protective factor against masticatory dysfunction. 4,10,12,[51][52][53][54][55][56][57][58] Studies observed significant increases in prefrontal activity, masticatory muscle activity and occlusal force when wearing a denture, compared to non-denture wearers having marked prefrontal deactivation, decreased masticatory muscle activity and occlusal force. 53 A randomised controlled trial also revealed that both balanced and lingualised occlusal schemes in removable dentures had an equal positive effect on food comminution.…”
Section: Re Sultsmentioning
confidence: 99%
“…These findings could support our observation that muscle-related factors affect masticatory performance. Furthermore, it has been reported that the decrease in masseter muscle thickness can negatively affect masticatory performance [ 22 ]. According to another study, the masseter muscle thickness may decrease as the appendicular skeletal muscle mass decreases [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated by applying a linear multiple regression model from G*power 3.1 software (Heinrich-Heine-University Düsseldorf, Düsseldorf, Germany). Based on the results of our preliminary study [ 22 ], the number of participants was calculated to be 73, with an effect size (f 2 ) of 0.15, an alpha level of 0.05, and a power of 90%. Estimating a dropout rate of about 20%, the total enrollment size was determined to be 88.…”
Section: Methodsmentioning
confidence: 99%
“…Advancing age in adulthood, independent of AD, is generally associated with an increase in dysbiosis [ 35 ] in the oral microbiome, with an increased abundance of bacteria associated with periodontal disease [ 36 ], in addition to fungal species, Candida Albicans [ 37 ], which causes oral thrush. This increased disease potential oral environment in older age is driven by reduced production and quality of saliva, which hampers the buffering capacity of the oral environment and lessens oral microbial clearance [ 36 ], in addition to declining nutritional quality [ 37 ], which reduces diversity of available macronutrients and is driven by reduced masticatory function, tooth loss, and potentially impaired taste perception [ 38 ].…”
Section: The Oral Microbiome and Admentioning
confidence: 99%